Therapeutic effect of prolonged testosterone pretreatment in women with poor ovarian response: A randomized control trial - Hoang, Quoc Huy; Ho, Hung Sy; Do, Huong Thuy; Nguyen, Tien Viet; Nguyen, Phuong Hong; Le, Minh Tam (John Wiley & Sons, 2021)
Purpose: This study compared the therapeutic effects of transdermal testosterone gel (TTG) application at 4 and 6 weeks before controlled ovarian hyperstimulation (COH) in women with poor ovarian response (POR). Methods: In this randomized control trial, infertile women with POR who underwent in vitro fertilization (IVF) were recruited and randomly classified into 4 week (n = 42) and 6 week (n = 38) TTG treatment groups and control group (n = 42). The primary outcome was total number of retrieved mature oocytes. The secondary outcomes were the biochemical pregnancy rate, clinical pregnancy rate, and ongoing pregnancy rate. Results: No significant differences were observed in the number of oocytes retrieved, mature oocytes and embryos between all groups. Human chorionic gonadotropin (hCG) positive, clinical, and ongoing pregnancy rates were significantly higher in the TTG pretreatment groups than in the control group but no differences were observed between the 4‐ and 6 week groups. Conclusions: Applying TTG in infertile women with POR may ameliorate the outcomes of IVF. The extended application of TTG to 6 weeks did not improve the response to ovarian stimulation regarding the number of retrieved oocytes nor pregnancy outcomes compared to the 4 week pretreatment.